1996
DOI: 10.1364/ao.35.003992
|View full text |Cite
|
Sign up to set email alerts
|

Tunable infrared laser detection of pyrolysis products of explosives in soils

Abstract: A research program involving two applications of tunable infrared laser differential absorption spectroscopy (TILDAS) with multipass, long-path absorption cells to the detection of explosives contamination in soils is reported. In the first application, sensitive, specific real-time species concentration measurements by TILDAS have led to new understanding of the processes involved in explosives detection by the heating of contaminated soils and the quantification of the resulting pyrolysis gases. In the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We note here that the current technique of detecting soil contamination by energetic materials also relies on fragmentation (78,135,136). A cone penetrometer probe is driven into the ground with a heated section that carries out the thermal decomposition.…”
Section: Fragmentation and Fragment Detectionmentioning
confidence: 99%
“…We note here that the current technique of detecting soil contamination by energetic materials also relies on fragmentation (78,135,136). A cone penetrometer probe is driven into the ground with a heated section that carries out the thermal decomposition.…”
Section: Fragmentation and Fragment Detectionmentioning
confidence: 99%
“…Laser-based sensors are being developed in the laboratory which can be incorporated into a SCAPS probe. Previously in this article, we have described the detection of explosive pyrolysis products from soil detected by TILDAS (38) (Figure 2 and Table 3) and the detection of TNT in soil by PF/LIF spectroscopy (134 -136) (Figure 12 and Table 6). In the following paragraphs, some of the applications of SCAPS for explosives detection for environmental application along with analytical methods are discussed.…”
Section: Environmental Applicationsmentioning
confidence: 97%
“…Thus, IR spectroscopy is a good confirmatory test if sufficient quantity of sample is available. Wormhoudt et al (38) have reported their efforts to develop a tunable infrared laser differential absorption spectroscopy (TILDAS) system for in situ identification of the presence of explosives in subsurface soil. (39) In laboratory tests, a 900°C pyrolyzer ring heater was placed a short distance (about 0.25 cm) from the soil surface and the soil was heated for periods of the order of minutes.…”
Section: Tunable Infrared Laser Differential Absorption Spectroscopy mentioning
confidence: 99%
“…Explosives represent only one area of concern, as the same sensing technology could be easily adaptable to the general class of threat agents that includes nuclear, biological, and environmental toxins. The ideal detection system for threat agents, whether these threats are explosives, chemical and biological agents, or illicit drugs, would possess high sensitivity (i.e., be capable of detecting threats present only at trace levels), be able to discern a threat amidst a real world background, possess a standoff capability, be straightforward to operate, and possess a real time sensing potential [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This last operational criterion will be critical whether the sensor is deployed at a military checkpoint, for airport security, or for any other domestic application where impeding the flow of commerce is an issue.…”
Section: Introductionmentioning
confidence: 99%